Organizational Culture Factors that Can Influence Knowledge Transfer - Ioan Pastor (EIRP Proceedings, 2011)
The paper tries to establish the correlation that exists between the types of organizational culture and the factors that influence knowledge transfer. We started from the hypothesis that organizations which have high scores for cultural factors of openness to change and innovation as well as for task-oriented organizational growth will have the tendency of being favourable to knowledge transfer. Moreover, we started from the hypothesis that organizations that have high scores for bureaucracy and competition factors will have the tendency of being unfavourable to knowledge transfer. The research reached the conclusion that there seems to be a correlation between organizational culture and the factors that influence knowledge transfer.